Excellent microwave absorption properties of Fe ion-doped SnO2/multi-walled carbon nanotube composites. Issue 48 (26th April 2016) - Xing, Honglong; Liu, Zhenfeng; Lin, Ling; Wang, Lei; Tan, Dexin; Gan, Ying; Ji, Xiaoli; Xu, Guocai
Abstract : Fe ions doped SnO2 /MWCNTs composites with 48.8% Fe ions doping content showed the maximum reflection loss was −44.54 dB at 15.44 GHz, and the maximum absorption bandwidth of reflection loss below −10 dB was 4.5 GHz in the Ku band. Abstract : In this work, Fe ion-doped SnO2 /multi-walled carbon nanotubes (MWCNTs) composites were synthesized using a hydrothermal method. X-ray diffraction, TEM, Raman and X-ray photoelectron spectroscopy, and vector network analyses were conducted to demonstrate the structure, interaction, morphology, chemical content, and electromagnetic parameters of the Fe ion-doped SnO2 /MWCNTs composites. The as-structured Fe ion-doped SnO2 /MWCNTs composites were proven to be outstanding lightweight microwave absorbers when the Fe ion doping percentage was relatively high. Fe ion doping at a molar percentage of 48.8% resulted in a maximum reflection loss (RL) of −44.5 GHz at 15.44 GHz with a layer thickness of 1.5 mm. The maximum RL ≤ −10 dB reached 4.5 GHz at the Ku band. The excellent microwave absorption of the as-prepared composites was principally due to proper attenuation and impedance matching, electric polarization, interfacial polarization, and conductive network. Such composites may have further applications in microwave absorption.